A Thematic Reading in the Thematic Poem (Suwaid Bin Abi Kahl Al-Yashkari) - Al-Osaimi, Theeb (Journal of Umm Al-Qura University for Language Sciences and Literature, 2024)
This research deals with a pre-Islamic poetic text, the poem of Suwaid bin Abi Kahl al-Yashkari, and approaches it objectively by searching for its prominent objective themes and the relations between them, as well as the basic theme that controlled the rest of the poetic text. Then, the research attempts to reveal the space of the poetic text, based on the importance of space in the formation of literary work, whether that space is in the place, the other, or textual space, which enables the text to interact with other texts and draws from them to form a new network of verbal and moral relationships. The research also tries to track the images that have emerged in the text and the search for their effect in revealing the relationship of the text to its creator, the effect of the process of consciousness and unconsciousness, and how this drew its relationship to the universe and existence.